The Influence of Board of Directors on Earnings Management - Meng, Linan (2022)
This dissertation investigates the effects of board of directors on earnings management in the firm based on the information from all Chinese listed firms during 2016-2020. In this research, modified Jones model is utilized to measure the extent of earnings management that is represented by discretionary accruals in the model. As the independent variable, board of directors is analyzed in five respects including independence of board, size of the board, CEO duality, the percentage of female directors and board activity. Then, three quantitative analysis methods are used in analyzing the research data and obtaining the results. Also, the robust test is performed to further check the results. The analysis results reflect that both board independence and board size have a significantly negative impact on managers’ opportunistic activities. However, there is no obvious connection between CEO duality and earnings management behaviors. Meanwhile, this research also shows that the number of female directors has no significant impact on managers’ earnings management practices. However, the number of board meetings shows a positive influence on managers to manipulate earnings which is different with some of prior papers. In general, this research could provide more evidence for prior studies, although some findings are not consistent with common thoughts. Also, the limitations in this dissertation could offer some suggestions for future research. Keywords: Board of Directors, Earnings Management, Chinese Listed Companies.